Why Software Professionals Knowingly Omit Appropriate Development Quality Practices? Control Balance Viewpoint - Moody, Gregory; Siponen, Mikko; Vartiainen, Tero (Springer Science+Business Media, 2026)
While software bugs and vulnerabilities are common — often considered unavoidable due to software complexity — previous studies also suggest deficiencies arise when professionals knowingly omit quality steps or take 'quick and dirty' shortcuts. We used a mixed‑methods approach to examine developers’ knowing omission of appropriate quality practices. First, we interviewed SW professionals who admitted to knowingly omitting relevant tests and coding practices and replacing them with questionable SW development shortcuts. The interviews implied that control balance theory (CBT)—control deficient and surplus provocations – could explain some of the omissions. Finally, we tested our contextualized CBT model, which explains omissions of appropriate SW development quality practices, SW professionals (n = 402). The results confirmed our model. The study contributes to SW development research by offering one potential explanation why SW professionals knowingly engage in low-quality practices when they are aware of better practices.
Keywords: Management of IT human resources; Systems design and implementation; Control balance theory; Software testing; fi=Tietojärjestelmätiede|en=Information Systems Science|